The Physico-Mechanical Properties and Release Kinetics of Eugenol in Chitosan-Alginate Polyelectrolyte Complex Films as Active Food Packaging - Baiq Amelia Riyandari; Suherman Suherman; Dwi Siswanta (Indonesian Journal of Chemistry, 2018)
A study of eugenol release and its kinetics model from chitosan-alginate polyelectrolyte complex (PEC) films has been conducted. Some factors that affected the eugenol release were also studied, including the composition of chitosan-alginate PEC and the concentration of eugenol. The chitosan-alginate-eugenol PEC films were synthesized at pH ± 4.0, then the PEC films were characterized using a Fourier-transform infrared spectroscopy (FTIR) spectrophotometer. An investigation of the films’ properties was also conducted, including morphology analysis using a scanning electron microscope (SEM), differential thermal analysis (DTA) / thermogravimetric analysis (TGA), mechanical strength, transparency testing, water absorption, and water vapor permeability. The release of eugenol was investigated through in vitro assay in ethanol 96% (v/v) for four days, and the concentration of eugenol was measured using an ultraviolet-visible (UV-Vis) spectrophotometer. The characterization of the films using FTIR showed that the formation of PEC occurred through ionic interaction between the amine groups (–NH3+)of the chitosan and the carboxylate groups (–COO–) of the alginate. The result showed that the composition of chitosan-alginate PEC and the concentration of eugenol can affect the release of eugenol from PEC films. A higher concentration of alginate and eugenol could increase the concentration of eugenol that was released from the films. The mechanism for the release of eugenol from chitosan-alginate PEC films followed the Korsmeyer-Peppas model with an n value of < 0.5, which means the release mechanism for eugenol was controlled by a Fickian diffusion process. The antioxidant activity assay of the films using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method resulted in a high radical scavenging activity (RSA) value of 55.99% in four days.